2022
DOI: 10.1177/19458924221098847
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Polysaccharide Relieves Inflammatory Responses in Guinea Pigs with Allergic Rhinitis via Ameliorating NF-kB-Mediated Treg/Th17 Imbalance

Abstract: Background Allergic rhinitis (AR) is regarded as a prevalent and non-infectious inflammation in nasal mucosa, and astragalus polysaccharide (APS) could mitigate inflammation. Objectives Herein, this study probed the specific mechanism of APS in inflammatory responses in AR. Methods Firstly, AR guinea pig models were established through the stimulation and sensitization of ovalbumin (OVA) and received APS treatment. Changes in nasal symptoms were assessed through counting the sneezing and rubbing times of guine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…NF-κB is an important transcription factor present in multiple inflammatory networks and plays a key role in regulating immune responses and cytokine activity in airway pathology. 21,22 The inhibition of inflammatory response by saffron through the NF-κB pathway has been confirmed in inflammatory diseases such as asthma, chronic obstructive pulmonary disease, atopic dermatitis, and arthritis. 23,24 Also, saffron and its pharmacologically active components play protective roles in the pathogenesis of inflammatory diseases such as digestive system diseases, atopic dermatitis, atherosclerosis, and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is an important transcription factor present in multiple inflammatory networks and plays a key role in regulating immune responses and cytokine activity in airway pathology. 21,22 The inhibition of inflammatory response by saffron through the NF-κB pathway has been confirmed in inflammatory diseases such as asthma, chronic obstructive pulmonary disease, atopic dermatitis, and arthritis. 23,24 Also, saffron and its pharmacologically active components play protective roles in the pathogenesis of inflammatory diseases such as digestive system diseases, atopic dermatitis, atherosclerosis, and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies had reported APS played a vital role in inflammatory responses under a variety of pathological conditions. 28 Prior experimental pieces of evidence demonstrated APS alleviated LPS-induced inflammation via the NF-κB/MAPK signaling pathway, and decreased the expression of IL-Iβ, IL-6 and TNF-α. 21 Meanwhile, APS could protected renal function and affected the TGF-β/Smad pathway in STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Following a one-week acclimation period, the animals were divided into five groups, each consisting of 8 members: the normal control group (NC), the group with OVA-induced allergic rhinitis (OVA), the OVA group of guinea pigs treated with berberine at a dosage of 25 mg/kg (OVA + LBer), the OVA group of guinea pigs treated with berberine at a dosage of 50 mg/kg (OVA + MBer), and the OVA group of guinea pigs treated with berberine at a dosage of 100 mg/kg (OVA + HBer). The allergic rhinitis model was established by sensitizing and stimulating the guinea pigs with OVA, following a method described in a previous study 22 . In short, the guinea pigs in the OVA group were sensitized by receiving OVA (25 μg/guinea pig) injections into their peritoneal cavity three times per week for a period of two weeks.…”
Section: Methodsmentioning
confidence: 99%